Plurilingual School and University Curricula - Schlabach Joachim; Hufeisen Britta (Peter the Great St. Petersburg Polytechnic University, 2025)
This contribution introduces plurilingual curricula as a development tool geared both to linking up the curricula of individual languages and fostering cross-linkages between language and content subject curricula. This approach represents a solid fundament for tertiary language didactics and can also supply a common foundation for school and university language learning policies and relevant school-university cooperation projects. The principle underlying (genuinely!) plurilingual university courses based on research and featuring a doubly multilingual didactic approach is explored. This is followed by discussion of the scope and design of a new research project accompanying the implementation of a plurilingual curriculum at a school in Liechtenstein.